The effects of teacher’s differentiated instructions based on students’ learning styles on their motivation. M.A Thesis Linguistics: - Nguyen, Thị Thịnh (University of Languages and International Studies, 2017)
This paper reports an action research undertaken in a reading course for second-year English majors in a university in Hanoi, Vietnam. Involving a group of twenty-six sophomores from the same class, this study aims to 1)identify the given class‟s learning styles and current level of academic motivation.